Financial Crises A Selection of Readings - Markoulis, Stelios (IntechOpen, 2021)
This book on financial crises is written at a time when the whole world is facing another crisis, a different one this time; one that is related to our health, as well as the economy in a painful manner. The first chapter of this book focuses on the economic effects of this crisis with particular emphasis on the financial sector. The remainder of the book presents a selection of readings related to the GFC. These touch upon issues such as corporate governance; the effect of the collapse of the Lehman Brothers on the net-worth of financial and non-financial firms; securitization and why the alchemy "did not work"; and finally, a case-study on Turkey and in particular the Turkish short-term interest rates and exchange rates and their relationship to political developments.